Prove that a2b2c2-ab-bc-ca is always non-negative for all valuesof a, b and c.
Answers
Answered by
2
HEY!!
a2 + b2 + c2 - ab - bc - ca
= (1/2)(2a2 + 2b2 + 2c2 - 2ab - 2bc - 2ca)
= (1/2)(a2 - 2ab + b2 + b2 - 2bc + c2 + c2 - 2ca + a2)
= (1/2)[(a-b)2 + (b-c)2 + (c-a)2]
Now we know that, the square of a number is always greater than or equal to zero.
Hence, (1/2)[(a-b)2 + (b-c)2 + (c-a)2] ≥ 0 =
it is always non-negative.
a2 + b2 + c2 - ab - bc - ca
= (1/2)(2a2 + 2b2 + 2c2 - 2ab - 2bc - 2ca)
= (1/2)(a2 - 2ab + b2 + b2 - 2bc + c2 + c2 - 2ca + a2)
= (1/2)[(a-b)2 + (b-c)2 + (c-a)2]
Now we know that, the square of a number is always greater than or equal to zero.
Hence, (1/2)[(a-b)2 + (b-c)2 + (c-a)2] ≥ 0 =
it is always non-negative.
Answered by
3
Here is your answer
Hope it helps you
Hope it helps you
Attachments:
![](https://hi-static.z-dn.net/files/d03/6290d86280eb4344827b6a6e497d7880.jpg)
Similar questions